ORNAMEN PURA PENATARAN BUJANGGA SANGGING PRABANGKARA BANJAR KEBON KECAMATAN BLAHBATUH GIANYAR PERSPEKTIF PENDIDIKAN SENI RUPA KEAGAMAAN HINDU - I Nyoman Putra Adnyana; I Kadek Sumadiyasa (WIDYANATYA, 2019)
Ornaments of Penataran Bujangga Sangging Prabangkara Temple Kebon Village Blahbatuh Gianyar, is one of the forms of Hindu religious fine art education which is very unique in its visual working process hereditary done incompletely as a means of religious belief, in its development become a phenomenon in its field. So it is interested to be examined under the title "Ornaments of Penataran Bujangga Sangging Prabangkara Temple Kebon Village, Blahbatuh District, Gianyar Perspective of Hindu Religious Fine Arts Education". With the formulation of the problems 1). Why Ornaments of Penataran Bujangga Sangging Prabangkara Temple are done incompletely/unfinished. 2). What is the shape of the ornaments of Penataran Bujangga Sangging Prabangkara Temple 3). What are the values ​​of Hindu Religious Fine Arts Education contained in the ornaments of Penataran Bujangga Sangging Prabangkara Temple. In the discussion, it was found that why Ornaments in Bujangga Sangging Prabanggkara Temple were done in incomplete/unfinished because of the Trust Systems to the ancestors, as a hereditary tradition. Unique Specific Ornament Forms, Imperfect Forms on; Gelung Kori Ornaments, Bale Kukul Ornaments, Masceti Pelinggih Ornaments, Monument Ornaments, 2 Pengadangan Monument Ornaments. Elements of fine art found in the ornamentation of Penataran Bujangga Sannging Prabangkara Temple; Curved Lines, Flat Lines, Slanted Lines, Straight Lines, Balance and Contrast. The values of fine art education and Hindu religious ornaments; Ethic education: Sangging attitude, aesthetic: Unity, Balance, Contrast, Accents. Social: community social, cooperation. Religious: forms of religious objects.